Block-and-fault dynamics modelling of the Himalayan frontal arc: Implications for seismic cycle, slip deficit, and great earthquakes. (15th October 2017) - Vorobieva, Inessa; Mandal, Prantik; Gorshkov, Alexander
Graphical abstract: Highlights: A new block-and-fault dynamics model is developed for the Himalayan frontal arc, India. Synthetic large earthquakes show same location and magnitudes as reported in earthquake catalogue. The seismic cycles for large synthetic earthquakes are found to be varying from 700 to 2100 years. Maximum hazard is modelled for the central GAP region of the Himalaya. While minimum hazard is modelled for the Kashmir and Assam Himalaya. Abstract: A numerical block-and-fault dynamics model (BAFD) of the Himalayan frontal arc, India is developed to understand the long-term patterns of strain accumulation and occurrences of great earthquakes in the Himalaya. The morphostructural scheme outlines twelve major crustal blocks, and external driving motions are prescribed using GPS data. The BAFD model reproduces essential features of the geodynamics and seismicity of the Himalayan frontal arc. The locations of the large synthetic earthquakes and their maximum magnitudes are consistent with the information available from the instrumental and historical earthquake catalogues. We model the evolution of the slip deficit and seismic cycles for different sections across the Himalaya frontal arc. The modelled seismic cycles are found to be varying from 700 to 2100 years and are in good agreement with the return periods estimates from the recent paleoseismological studies. We notice that the accumulation of the slip deficit depends not only on the rate of shortening, rheology and structure but also on the dynamics of the confining crustal blocks. Further, we observe that tectonic motions of the Shillong plateau and Assam basin microplates play a significant role in controlling the seismicity patterns of the Bhutan block, which resulted in the decreased seismic activity, and increased rate of aseismic displacement. Thus, we infer that the regional seismicity patterns are a consequence of dynamics of the entire regional fault-and-block system rather than dynamics of individual fault. Our BAFD modelling predicts the maximum earthquake hazard associated with future large/great earthquakes for the central Himalayan gap region, which lies between the 1905 Kangra and the 2015 Gorkha earthquake ruptures, but relatively less hazard in Kashmir and Assam.